BAUN score, a better predictive model of in-hospital and long-term outcomes in acute heart failure?. (14th October 2021) - Santos, J; Pires, I; Neto, V; Goncalves, L; Correia, J; Almeida, I; Correia, E
Abstract: Introduction: Patients hospitalized due to acute heart failure (AHF) compose a heterogeneous population whose prognosis is difficult to forecast. Previously, BAUN score has proven to be able to accurately predict in-hospital mortality (IHM) in AHF. We aimed to evaluate BAUN score performance in the prediction of long-term outcomes in this population, comparing it to the recently validated Get With The Guidelines (GWTG) score. Methods: A retrospective analysis of 1052 patients admitted to a Cardiology ward due to AHF was performed. 268 patients were excluded due to data omission or therapy with sacubitril/valsartan. Using the variables systolic blood pressure, urea, brain natriuretic peptide and sodium at admission, BAUN score was calculated, ranging from 0–28 points. GWTG score was also calculated at the index event. ROC curve analysis was used to compare the predictive value of the two scores for IHM. Kaplan-Meyer and Cox-regression analysis were performed to evaluate BAUN score prediction ability for 24-month mortality (24-MM) and for the composite endpoint of 24-month rehospitalization or death (24-MH). Results: Mean patient age was 77 (±10) years; 51% were men. Mean left ventricle ejection fraction (EF) was 49% (±16.4). An EF<40% was present in 31% of patients. IHM, 24-MM and 24-HM were 6.5%, 17.1% and 57.8%, respectively. Mean BAUN score was 7 (±5.64). Mean GWTG score was 49.7 (±9.8). ROC curve analysis for IHM prediction revealed a better performance of the BAUN score (AUC: 0.738p, <0.001) in comparison with GWTG score (AUC: 0.687, p<0.001). Patients were stratified into subgroups according to BAUN risk score – very-high risk (≥22), high risk (16–21), intermediate risk (5–15) and low risk (<5). Kaplan-Meyer analysis revealed a significant difference in 24-MM according to risk subgroup (very high: 35%, high: 26.7%, intermediate: 19.5%, low risk: 12.7%, χ 2 =16.304, p=0.001). When stratified by non-reduced or reduced EF (≥40% or <40%), there was still a significant mortality difference in subgroups with reduced (p=0.007) and borderline significant in patients with nonreduced EF (p=0.05). Kaplan-Meyer analysis also revealed a significant difference between subgroup risk for 24-MH (51%; 63.8%; 63.3% and 75%, respectively, for low, intermediate, high and very-high risk, χ 2 =21.237, p<0.001). Cox regression analysis demonstrated that BAUN score independently predicts 24-MM (HR: 1.056, p=0.043) and 24-MH (HR: 1.033, p=0.048), even after adjustment for other prognostic markers, such as atrial fibrillation, coronary artery disease, previous myocardial infarction, age, EF and GWTG score. Conclusion: BAUN outperforms GWTG score for IHM prediction in AHF. It also independently predicts 24-MM and 24-MH. Its use may identify patients with high risk of mortality/readmission, in need of specialized care, and those patients with low risk of death, who might be candidates for lenient surveillance. Funding Acknowledgement: Type of funding sources: None.